Impact of Employment Support Programs on the Quality of Youth Employment: Evidence from Senegal's Internship Program - André Dumas Tsambou; Thierno Malick Diallo; Benjamin Fomba Kamga; Simplice Asongu (African Governance and Development Institute (AGDI), 2023)
Youth unemployment is major policy concern in Senegal. The country has in recent years, implemented several programs to combat unemployment and the precariousness of youth employment in the labor market. However, the results of these programs are to date hardly perceptible. The objective of this work is to assess the impact of employment support programs on the quality of youth employment. We provide empirical evidence of the effect of the apprenticeship program implemented by the National State-Employer Convention in facilitating youth access to quality employment. Job quality is determined using an index that captures multiple wage and non-wage dimensions of job quality. Using survey data on the improvement of employment policies from 2746 individuals, we use the endogenous switching regression method and the propensity score matching method to assess and compare the impact of the apprenticeship program on the quality of jobs held by young men and women. The results show that the apprenticeship program has a positive and significant impact on job quality. Indeed, we find that the quality of employment is better for young men and women who benefited from the internship program than for those who did not. We find, however, that there is a difference in job quality between males and females who received the program. The differences in job quality are explained more by differences in job characteristics but are not directly related to gender or age.
Keywords: J4; E24; O55; M53; 330; Youth; Labor market; quality of employment; Senegal; Apprenticeship